Transforming early English the reinvention of early English and older Scots - Smith, J. J. 1955- (Cambridge University Press, 2020)
Prologue : snatched from the fire : the case of Thomas Percy -- On historical pragmatics -- Inventing the Anglo-Saxons -- 'Witnesses preordained by God' : the reception of Middle English religious prose -- The great tradition : Langland, Gower, Chaucer -- Forging the nation : reworking older Scottish literature -- On textual transformations : Scott and beyond.
Keywords: Historische Pragmatik; Schottisch; Sprachentwicklung; Englisch; Sprachwandel; Altenglisch; Historische Sprachwissenschaft; English language / History; Historical linguistics